Diagnostic Errors in Pediatric Critical Care: A Systematic Review*. Issue 8 (August 2021) - Cifra, Christina L.; Custer, Jason W.; Singh, Hardeep; Fackler, James C.
Abstract : OBJECTIVES: To summarize the literature on prevalence, impact, and contributing factors related to diagnostic error in the PICU. DATA SOURCES: Search of PubMed, EMBASE, and the Cochrane Library up to December 2019. STUDY SELECTION: Studies on diagnostic error and the diagnostic process in pediatric critical care were included. Non-English studies with no translation, case reports/series, studies providing no information on diagnostic error, studies focused on non-PICU populations, and studies focused on a single condition/disease or a single diagnostic test/tool were excluded. DATA EXTRACTION: Data on research design, objectives, study sample, and results pertaining to the prevalence, impact, and factors associated with diagnostic error were abstracted from each study. DATA SYNTHESIS: Using independent tiered review, 396 abstracts were screened, and 17 studies (14 full-text, 3 abstracts) were ultimately included. Fifteen of 17 studies (88%) had an observational research design. Autopsy studies (autopsy rates were 20–47%) showed a 10–23% rate of missed major diagnoses; 5–16% of autopsy-discovered diagnostic errors had a potential adverse impact on survival and would have changed management. Retrospective record reviews reported varying rates of diagnostic error from 8% in a general PICU population to 12% among unexpected critical admissions and 21–25% of patients discussed at PICU morbidity and mortality conferences. Cardiovascular, infectious, congenital, and neurologic conditions were most commonly misdiagnosed. Systems factors (40–67%), cognitive factors (20–3%), and both systems and cognitive factors (40%) were associated with diagnostic error. Limited information was available on the impact of misdiagnosis. CONCLUSIONS: Knowledge of diagnostic errors in the PICU is limited. Future work to understand diagnostic errors should involve a balanced focus between studying the diagnosis of individual diseases and uncovering common system- and process-related determinants of diagnostic error. Abstract : Supplemental Digital Content is available in the text.